Inferior Frontal Gyrus-Based Resting-State Functional Connectivity and Medium Dispositional Use of Reappraisal Strategy - Li, Wenjuan; Xie, Ke; Ngetich, Ronald K.; Zhang, Junjun; Jin, Zhenlan; Li, Ling (Frontiers in Neuroscience, 2021)
The previous neuroimaging functional connectivity analyses have indicated that the inferior frontal gyrus (IFG) is associated with better emotion regulation in reappraisal tasks. However, no study has explored the relationship between IFG-based resting-state functional connectivity (rsFC) and the dispositional use of reappraisal strategy. Therefore, the present study examined the potential associations between rsFC patterns of both left and right IFG and dispositional reappraisal use. One hundred healthy participants completed the Emotional Regulations Questionnaire (ERQ) and underwent a resting-state functional magnetic resonance imaging (fMRI) acquisition. Our findings showed that IFG-based rsFC was positively correlated with dispositional reappraisal only in the range of 4 to 5.5 points (medium reappraisal group, MRG). Specifically, medium dispositional reappraisal was positively correlated with rsFC between left/right IFG and bilateral temporal gyrus. Besides, medium dispositional reappraisal was positively correlated with rsFC between left IFG and bilateral superior parietal lobe (SPL), middle cingulate cortex (MCC) and right insula, as well as between right IFG and dorsomedial prefrontal cortex (DMPFC), and anterior cingulate cortex (ACC). In conclusion, these results indicate that bilateral IFG plays an important role in the medium use of the reappraisal strategy.